Diagnosing human blood clotting deficiency - Ong, C.C. (Elsevier B.V., 2018)
There are different clotting factors present in blood, carries the clotting cascade and excessive bleeding may cause a deficiency in the clotting Diagnosis of this deficiency in clotting drastically reduces the potential fatality. For enabling a sensor to detect the clotting factors, suitable probes such as antibody and aptamer have been used to capture these targets on the sensing surface. Two major clotting factors were widely studied for the diagnosis of clotting deficiency, which includes factor IX and thrombin. In addition, factor IX is considered as the substitute for heparin and the prothrombotic associated with the increased thrombin generation are taking into account their prevalence. The biosensors, surface plasmon resonance, evanescent-field-coupled waveguide-mode sensor, metal-enhanced PicoGreen fluorescence and electrochemical aptasensor were well-documented and improvements have been made for high-performance sensing. We overviewed detecting factor IX and thrombin using these biosensors, for the potential application in medical diagnosis. Â© 2018 Elsevier B.V.